Transformasi Musik Balaganjur Teruna Goak Ke dalam Musik Jazz - Firdaus, Ade Surya; Santosa, Hendra; Ardini, Ni Wayan (PANGGUNG, 2019)
ABSTRACT           The Megoak-goakan tradition from a Panji Village is played with Balaganjur Teruna Goak music, both of which are very interesting when they are transformed into jazz because they have the same basic musical form. This article aims to provide an overview of the process of transformation of Balaganjur Teruna Goak Village in Panji Village into jazz music. The process of transformation into jazz music was carried out with the creation method of exploratory which began with a literature study on the Megoak-goakan tradition in Panji Village, Buleleng, and then conducted participant observations, interviews, and continued with experiments on various musical motifs which were considered suitable with a jazz music. The results are obtained from observing and analyzing the process using the theory of basic form of music of Pono Banoe and Prier’s. It is found that Balaganjur Teruna Goak's music had a lively expression with the phrases of antecedent (question) and consequent (answer). Furthermore, the experimental stage begins with pouring musical inspiration that is used in this work in several stages through writing notation. The formation step is done by assembling existing motifs and then formed into a unified whole composition. The creation of jazz music is based on Balaganjur music, and in its creating processes does not neglect the work of others so that it is possible that in its motifs and patterns on musical arrangements have adopted the previous works.Keyword: Teruna Goak, Balaganjur, Jazz Music, Transformation, Panji VillageABSTRAK           Tradisi Megoak-goakan dari Desa Panji dimainkan dengan musik Balaganjur Teruna Goak. Keduanya sangatlah menarik jika ditransformasikan ke dalam musik jazz karena memiliki bentuk dasar musik yang sama. Artikel ini bertujuan memberikan gambaran bagaimana proses transformasi musik Balaganjur Teruna Goak Desa Panji ke dalam musik jazz. Proses transformasi ke dalam musik jazz dilakukan dengan metode penciptaan dari penjajakan yang diawali dari studi literatur tentang tradisi Megoak-goakan di Desa Panji Buleleng, kemudian melakukan pengamatan langsung, wawancara, dan dilanjutkan dengan percobaan berbagai motif musik yang diperkirakan cocok dengan musik jazz. Hasil yang didapat dari pengamatan dan proses analisis menggunakan teori bentuk dasar musik Pono Banoe dan teori bentuk musik dari Prier. Musik Balaganjur Teruna Goak memiliki ekspresi yang bersemangat dengan frase antiseden (tanya) dan konsekuen (jawab). Selanjutnya, pada tahap percobaan dimulai dengan cara menuangkan inspirasi musik yang akan digunakan dalam garapan ini secara bertahap melalui penulisan notasi. Tahap pembentukan dilakukan dengan merangkai motif-motif yang telah ada kemudian dibentuk menjadi suatu kesatuan komposisi yang utuh. Penciptaan musik jazz yang berdasarkan musik Balaganjur ini, pada penggarapannya tidak mengabaikan hasil karya orang lain sehingga kemungkinan dari segi motif dan pola garap musikal mengadopsi yang sudah ada sebelumnya.Kata Kunci: Teruna Goak, Balaganjur, Musik Jazz, Transformasi, Desa Panji